In situ XPS investigation of VPO catalyst oxidation state at different catalytic conditions; BESSY Annual Report 2003 - Knop-Gericke A.; Teschner D.; Pestryakov A. N. Aleksey Nikolaevich; Kleimenov E.; Bluhm H.; Hävecker M.; Schlögl R.; Lopez-Sanchez J. A.; Bartley J. K.; Hutchings G. J. (2004, 2004)
В фонде НТБ ТПУ отсутствует